2017
DOI: 10.1289/ehp767
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Exposure to Household Air Pollution: A Systematic Review and Pooled Analysis of Carbon Monoxide as a Surrogate Measure of Particulate Matter

Abstract: Background:Household air pollution from solid fuel burning is a leading contributor to disease burden globally. Fine particulate matter (PM2.5) is thought to be responsible for many of these health impacts. A co-pollutant, carbon monoxide (CO) has been widely used as a surrogate measure of PM2.5 in studies of household air pollution.Objective:The goal was to evaluate the validity of exposure to CO as a surrogate of exposure to PM2.5 in studies of household air pollution and the consistency of the PM2.5–CO rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
63
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 99 publications
5
63
1
1
Order By: Relevance
“…In Ghana, a 1 ppm increase in CO exposure was associated with 0.4 mm Hg higher bSBP and bDBP in pregnant women with mean CO exposure of 1.6 ppm 20. Compared with our study, the smaller magnitude of association may be due to their younger participants (mean age=27 years) or measurement error with use of CO as a surrogate of PM 21. No previous studies have assessed HAP and central haemodynamics or arterial stiffness, preventing comparison.…”
Section: Discussioncontrasting
confidence: 87%
“…In Ghana, a 1 ppm increase in CO exposure was associated with 0.4 mm Hg higher bSBP and bDBP in pregnant women with mean CO exposure of 1.6 ppm 20. Compared with our study, the smaller magnitude of association may be due to their younger participants (mean age=27 years) or measurement error with use of CO as a surrogate of PM 21. No previous studies have assessed HAP and central haemodynamics or arterial stiffness, preventing comparison.…”
Section: Discussioncontrasting
confidence: 87%
“…Most studies to date have been conducted in LMICs including India, Guatemala, Pakistan, and Ghana, countries where other competing risk factors for adverse birth outcomes such as malnutrition, poverty, infections and poor access to health care, are highly prevalent (21,26). Further, in-home deliveries and limited access to prenatal care in rural regions may often result in gaps in information related to fetal growth and pregnancy-related complications making it difficult to control for residual confounding factors to estimate the true effect of HAP on fetal health.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Some studies reported a relatively strong correlation (Pearson's r > 0.8) between both pollutants, 35,36 while others found a weaker correlation, 18,37 especially at the level of personal exposure. 38 Based on our regression analysis, we can indicate that CO was strongly and significantly associated with the variation in PM 2.5 levels (P-value = 0.006) in the kitchen area. This would support the methodology used in other studies of household air pollution, which have estimated PM 2.5 from measurements made in CO concentrations.…”
Section: Discussionmentioning
confidence: 70%
“…From the measurements described in this paper, a baseline for indoor air quality and two predictive models were developed for rural kitchens in Paraguay. Some studies reported a relatively strong correlation (Pearson's r > 0.8) between both pollutants, 35,36 while others found a weaker correlation,18,37 especially at the level of personal exposure 38. Regression analysis showed that variables such as the kitchen structure and construction materials were not significant, while other factors, such as the community, cookstove usage, and the type of fuel used for cooking, were strong predictors of the indoor PM 2.5 and CO concentrations.…”
mentioning
confidence: 98%